Izdaja serijsko izdelanih ortoz pacientom v lekarnah in specializiranih prodajalnah - Horvat, Josip (Rehabilitacija (Ljubljana), 2012)
Background: Application of medical technical aids in Slovenia is regulated by the Health Security and Insurance law. Medical technical aids include prefabricated orthoses, intermediate products and custom made orthoses. The prefabricated orthoses that are offered to the insurance holders according to the regulations of the Health Insurance Institute of Slovenia (HIIS) in specialised shops and pharmacies have to be correctly chosen and adjusted. Adequate application of an orthosis requires knowledge of the anatomy, materials, purpose and function of the orthosis. A certified prosthetist and orthotist (CPO) acquires this knowledge during the study at the Faculty for Health Sciences, but CPOs are rarely employed in specialised shops and pharmacies. When reviewing the regulations from this field we did not find a regulation that would oblige the providers of medical technical aids to employ suitable professionals. The aim of our study was to find out who provides and fits orthoses in specialised shops and pharmacies, what solutions do they offer to the patient and how they approach resolving the patients problem. Methods: Four CPOs visited specialized shops and pharmacies that supply medical technical aids according to a contract with the HIIS. We introduced ourselves as patients or relatives of the patient and interviewed the staff. The structured interview was prepared beforehand. Results: We visited 22 offices. In the opinion of their staff, they all offered orthoses which do not require any further adjustment. In most of the offices they did not demand that the user of the orthosis should came to the office him/herself for application of the orthosis. Only one office employed a CPO.
Keywords: Amputation; knee orthosis; medical device; medicinski pripomočki; orthosis for foot drop; Orthotic devices; ortotski pripomočki; ortoze; Outcome assessment (health care); prefabricated orthosis; Rehabilitation; spinal orthosis